Unlocking potential: Enhancing science learning through workbook integration - Co, Annalene Grace E (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigated the effectiveness of using workbooks as supplementary instructional materials to enhance science learning among college students. A quasi-experimental pretest-posttest design was employed with two groups: an experimental group using traditional teaching methods supplemented with workbooks, and a control group receiving traditional instruction only. Data were collected from 68 freshmen students at a state university, including pre-test and post-test scores and academic performance (semi-quarterly and quarterly grades). Paired-samples t-tests and independent samples t-tests were conducted to analyze the data. The results demonstrated significantly higher post-test scores and improved academic performance in the experimental group compared to the control group. Effect size analyses indicated moderate to high practical significance for the use of workbooks in enhancing student learning. The study concludes that integrating workbooks into traditional teaching methods significantly enhances student learning outcomes in science. These findings underscore the importance of utilizing effective instructional materials. The study recommends that educational institutions prioritize the use of workbooks, ensure their effective utilization by teachers, and promote the development and evaluation of high-quality workbooks across various disciplines.